Revisiting the 'ideal victim' : developments in critical victimology - Christie, Nils, 1928-2015.; Duggan, Marian (Bristol : Policy Press, 2019)
Nils Christie's (1986) seminal work on the 'Ideal Victim' is reproduced in full in this edited collection of vibrant and provocative essays that respond to and update the concept from a range of thematic positions. Each chapter celebrates and commemorates his work by analysing, evaluating and critiquing the current nature and impact of victim identity, experience, policy and practice. The collection expands the focus and remit of 'victim studies', addressing key themes around race, gender, faith, ability and age while encompassing new and diverse issues. Examples include sex workers as victims of hate crimes, victims' experiences of online fraud, and recognising historic child sexual abuse victims in Ireland.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 10, 2018).
Keywords: Victims of crimes; Christie, Nils, -- 1928-2015.; True Crime; Social services & welfare, criminology